2015
DOI: 10.1371/journal.pone.0143432
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of Genetic Data Present in Bipolar Patients, but Absent in Control Persons

Abstract: The main objective of the study was to find combinations of genetic variants significantly associated with bipolar disorder. In a previous study of bipolar disorder, combinations of three single nucleotide polymorphism (SNP) genotypes taken from 803 SNPs were analyzed, and four clusters of combinations were found to be significantly associated with bipolar disorder. In the present study, combinations of four SNP genotypes taken from the same 803 SNPs were analyzed, and one cluster of combinations was found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 17 publications
(26 reference statements)
4
14
0
Order By: Relevance
“…However, in four studies of such combinations, no single combination was found to be significantly associated with the investigated disorder [7], [8], [10], [25]. Obviously, a combination that occurs only once in the study material will be present in either a patient or a control person, and such a combination will not be statistically significantly associated with a disorder.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…However, in four studies of such combinations, no single combination was found to be significantly associated with the investigated disorder [7], [8], [10], [25]. Obviously, a combination that occurs only once in the study material will be present in either a patient or a control person, and such a combination will not be statistically significantly associated with a disorder.…”
Section: Discussionmentioning
confidence: 91%
“…Among the 607 bipolar patients, 73 had at least one of these combinations in their genomes. These combinations were not found in the genomes of any of the 1355 control persons [8].…”
Section: Methods For Studying Combinations Of Genetic Variantsmentioning
confidence: 92%
See 3 more Smart Citations